SISTEM INFORMASI ABSENSI DAN PENGGAJIAN KARYAWAN MENGGUNAKAN RADIO FREQUENCY IDENTIFICATION (STUDI KASUS DI PT. WINDIKA UTAMA SEMARANG) - Muhammad Wachid Basyir (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
PT. Windika Utama Semarang has a problem that is all activities related to employee absence and payroll is not computerized properly, therefore a system is needed fully automated and managed by a computer by integrating the RFID system in it so leaders can monitor attendance and payroll with realtime per branch. This research uses the Research and Development (R&D) research method through the stages of study introduction, planning, product development, product design trials, product revisions, and product trials. Systembcreated using the Visual Basic 6.0 programming language, Ms. database. Access, Report Data Environment and RFID reader with tags as a tool for employee attendance.